2021
DOI: 10.1021/acs.jafc.0c07560
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polymer Eucommia Ulmoides Rubber: A Novel Material

Abstract: As the second natural rubber resource, Eucommia ulmoides rubber (EUR) from Eucommia ulmoides Oliver is mainly composed of trans-1,4-polyisoprene, which is the isomer of natural rubber cis-1,4-polyisoprene from Hevea brasiliensis. In the past few years, the great potential application of EUR has received increasing attention, and there is a growing awareness that the natural polymer EUR could become an emerging research topic in field of the novel materials due to its unique and excellent duality of both rubber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 203 publications
0
57
0
Order By: Relevance
“…These compounds coincide with those reported by Bhadra et al 2 who identified by GC–MS the polyisoprenes present in jackfruit latex. According to Wei et al 29 the transformation of polyisoprene molecules into limonene, as well as their oxidation products during pyrolysis, depends on the molecular weight (≥6000) and the abundance of the polymer, which indicates that EP‐6 shows a higher content of polyisoprenes.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds coincide with those reported by Bhadra et al 2 who identified by GC–MS the polyisoprenes present in jackfruit latex. According to Wei et al 29 the transformation of polyisoprene molecules into limonene, as well as their oxidation products during pyrolysis, depends on the molecular weight (≥6000) and the abundance of the polymer, which indicates that EP‐6 shows a higher content of polyisoprenes.…”
Section: Resultsmentioning
confidence: 99%
“…As the second natural rubber resource and one of the main components, E. ulmoides rubber, it is worth mentioning that although E. ulmoides rubber is not a novel isolated and discovered compound, in the past few years, the great potential application of E. ulmoides rubber has received increasing attention in the fields of the environment, agriculture, engineering, and biomedical engineering etc. Very recently, a comprehensive review summarized the novel applications of E. ulmoides in diverse fields [ 137 ].…”
Section: Novel Components Isolated From E Ulmoides and Their Biological Activitiesmentioning
confidence: 99%
“…Eucommia ulmoides is a relict plant deposited by quaternary glaciers. The bark, leaves, fruits and seeds of eucommia ulmoides all contain eucommia ulmoides rubber (EUG), which is a type of bio-based polymer material [ 10 , 11 ]. EUG, an isomer of natural rubber (NR), crystallizes at room temperature by the ordered trans arrangement.…”
Section: Introductionmentioning
confidence: 99%